On the winding pattern influence for filament wound cylinders under axial compression, torsion, and internal pressure loads - Menezes, Eduardo Antonio Wink (2023)
An intrinsic characteristic of components manufactured by the filament winding process is a winding pattern formation during the processing. This paper aims at unlocking and understanding how the winding pattern influences the mechanical behaviour of filament wound cylinders under different boundary conditions. To realize this, a series of finite element models followed by an original geometric approach to generate the pattern are herein developed. Four different patterns and six different winding angles are modelled. These are also modelled by varying the number of layers towards understanding whether there is a correlation between the pattern and the number of layers or not. Three loading cases are considered: axial compression, pure torsion, and internal pressure. Key results reveal that the more layers are stacked to the cylinder, the less impactful is the winding pattern to all loading cases herein investigated.